SERVICE QUALITY, ONLINE REVIEWS, AND BRAND IMAGE: DETERMINANTS OF CONSUMER PURCHASE DECISIONS ON SHOPEE - Primandaru, Noormalita; br Sembiring, Abira Rafasia; Nasution, Olivia Barcelona (Jurnal Manajemen, 2024)
The rapid advancement of technology in the digital era has significantly transformed the e-commerce landscape, particularly in Indonesia, where platforms like Shopee have gained immense popularity. This study investigates the impact of e-service quality, online reviews, and brand image on purchasing decisions among consumers in Yogyakarta. A quantitative approach was employed, utilizing questionnaires distributed to Shopee users who have made purchases. The data were analyzed using Partial Least Square (PLS) to assess the relationships between the variables. The findings reveal that e-service quality positively influences purchasing decisions, highlighting its importance in enhancing customer satisfaction and convenience while online shopping. In contrast, online reviews did not have a significant effect on purchasing decisions, suggesting that consumers may be skeptical about the authenticity of reviews or influenced by negative past experiences. Furthermore, brand image emerged as a critical factor, significantly affecting purchasing decisions, as a strong brand reputation fosters consumer trust and loyalty. This research emphasizes the need for e-commerce platforms to focus on improving service quality and maintaining a positive brand image to drive consumer purchasing behavior effectively.